Structure Design and Leg Kinematics Analysis of Scorpion Type Coke Oven Temperature Measuring Robots - Li Yaning; Gao Qiang; Yan Pengfei; Zan Xiaolei; Jiang Fangyu (Jixie chuandong)
A scorpion type robot is designed for the temperature measurement of coke ovens in response to the harsh environment on the top of the coke oven, low accuracy and efficiency of manual temperature measurement. This study mainly analyzes the design based on the robot's leg walking mechanism. Firstly, the biomimetic structure of the scorpion is referred to complete the modeling of the overall structure of the coke oven temperature measuring robot and the design of its legs. Stress analysis indicates that it operates safely and stably during the temperature measurement process. Secondly, the Denavit-Hartenberg (D-H) coordinate system of the robot's kinematic structure is established, and the forward and inverse kinematics of its legs are analyzed. Thirdly, the Matlab software is used to plan the Cartesian space trajectory of the legs, and Adams software is used to simulate the gait of the leg joints, indicating that the motion curves of the leg trajectory planning and gait simulation are almost identical and running smoothly. The experimental results show that the actual error of the temperature measurement robot's movement is maintained within 2 mm and runs smoothly. This lays an important foundation for the development of the overall system of the coke oven temperature measurement robot in the future.